Hubungan Pengetahuan Karier, Pengalaman Magang, dan Sikap dengan Minat Karier Perhotelan - Silvi Dwi Agustin; Henry Yuliamir (Mahesa Research Center, 2026)
This study examines the relationship between career knowledge, internship experience, and attitudes toward the hotel profession with students’ interest in pursuing a career in the hospitality industry using a quantitative correlational approach. The problem focuses on the low interest of some vocational high school students majoring in Hospitality to continue their careers in this sector despite having received education and internship experience. Data were collected through questionnaires distributed to 127 students of SMK N 1 Karimunjawa who had participated in an internship program, and were then analyzed using correlation tests and multiple linear regression with SPSS. The results indicate that all three variables have a positive and significant effect on students’ career interest, with internship experience being the most dominant factor. This study emphasizes the importance of strengthening career knowledge, implementing quality internship programs, and fostering professional attitudes to enhance students’ interest in pursuing a career in the hospitality field. The scientific contribution of this article lies in providing empirical evidence on the determinants of career interest among students in vocational hospitality education.